Actuating force for transmission controls in small farm tractor considering driver’s comfort - PRADHAN, NRUSINGH CHARAN; SAHOO, PRAMOD KUMAR; KUSHWAHA, DILIP KUMAR; MANI, INDRA; KUMAR, MOHIT (The Indian Journal of Agricultural Sciences, 2022)
Tractor drivers are exposed to a lot of physical and mental stress during field operations. In small tractor, less space is available in workspace for tractor driver. Therefore, proper design of controls in workspace of small tractor is imperative. A study was carried out at ICAR-Indian Agricultural Research Institute during 2021 to compare the workspace configuration of small tractor with Indian Standard IS 12343:1998 and measure force requirements of selected transmission controls. Most of the frequently used controls in the workspace of the selected tractor are located at a range less than recommendations of the Indian Standard IS 12343:1998. Force measurements of selected transmission controls were performed in a field of size 30 × 15 m2. Tractor was attached with three implements (i.e. rotary tiller, cultivator and planter) and operated by three different operators. It was observed that mean force requirement of brake and clutch pedals were high for small tractors due to difficulty in operator’s sitting. However, the force requirements of accelerator, driving shift and range shift gear lever were close to the recommended values. The frequency of use of controls was also estimated to determine number of times tractor driver applied certain control in a defined area. The driving shift gear lever and range shift gear lever were observed as the most and least frequently used controls respectively in the tractor workspace during field operations. The measured forces will be used to design the automatic system for selected controls in small tractor.